Impact of anticoagulation therapy on outcomes in patients with cardiac implantable resynchronization devices undergoing transvenous lead extraction: A substudy of the ESC‐EHRA EORP ELECTRa (European Lead Extraction ConTRolled) Registry. (29th April 2019) - Regoli, François; Auricchio, Angelo; Di Cori, Andrea; Segreti, Luca; Blomström‐Lunqvist, Carina; Butter, Christian; Deharo, Jean‐Claude; Kennergren, Charles; Kutarski, Andrzej; Laroche, Cecile; Zalevskiy, Valery; Luzzi, Giovanni; et al.
Abstract: Introduction: Little data are available on anticoagulation (AC) management in patients with cardiac resynchronization (CRT) devices who undergo transvenous lead extraction (TLE) procedure. We investigated the impact of AC on periprocedural complications in CRT patients undergoing TLE, enrolled in the ESC‐EHRA European Lead Extraction ConTrolled (ELECTRa) registry. Methods and Results: All CRT patients treated with TLE enrolled in the registry were considered. Perioperative AC management was left to the discretion of the Center. Major and minor intraprocedural and postprocedural complications were compared between patients without AC (Gp1) and patients with AC (Gp2). Regression analyses were performed to identify predictors of complications for Gp2. Out of 734 CRT pts, 328 (44.7%) were under AC (Gp2). Patients from Gp2 presented lower LVEF (Gp2 32.5 ± 10.9 vs Gp1 34.5 ± 11.9%; P = 0.03), more advanced heart failure disease (NYHA III/IV: Gp2 42.0 vs Gp1 31.5%; P = 0.02), and renal impairment (Gp2 39.0 vs Gp1 24.3%; P < 0.001). Perioperative regimens included AC interruption (Gp2A: n = 169, 51.5%), "bridging" (Gp2B: n = 135, 41.2%), or continued AC (Gp2C: n = 24, 7.3%). TLE complete success rates (98% in both groups) and major complication rates were comparable for both groups; minor bleeding events were more frequent in Gp2 (5.5%) compared to Gp1 (2.5%; P = 0.051). No independent predictors were identified for Gp2, but minor complications were associated with "bridging" approach (Gp2B: 16 events vs Gp2A/C: 9 events; P = 0.020). Conclusion: CRT patients treated with TLE under AC were more compromised but did not present more major complications compared to patients without AC. More minor complications were associated with "bridging" AC regimen.